Strategi Pengembangan Pariwisata Berbasis Masyarakat Lokal di Kampung Tanjung Siambang Kelurahan Dompak Kecamatan Bukit Bestari Kota Tanjungpinang - mandala, edward; RINAH, SRI AMBAR; EFFENDI, DESRIAN; SANJAYA, IRVAN DHARMA (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Tanjungpinang City is one of the cities located in the Riau Islands Province which is rich in tourism objects, while the potential for tourism objects in Tanjunpinang City are natural tourism, cultural tourism and artificial tourism. This is reinforced by the growth of foreign tourists visiting Tanjungpinang City in 2019 reaching 80,748 people from January to June. The importance of strategic management in tourism development, therefore researchers are interested in researching local community-based tourism development strategies in Tanjung Siambang Village, Dompak Village, Bukit Bestari District, Tanjungpinang City. This study uses a descriptive type of research. Where the researchers want to aim to explain the phenomena that occur in the field about tourism in Tanjung Siambang Tanjungpinang City by using a calibative method. The results of this study are where the SWOT analysis is an indication of various factors systematically to formulate company strategy. This analysis is based on a logic that can maximize Strengths and Opportunities, but simultaneously minimize Weaknesses and Threats, so from the results of the SWOT analysis on the development of local community-based tourism in Tanjung Siambang Village, it can be concluded that: said it was not running optimally. This can be identified regarding the strengths and weaknesses that come from the internal environment of the Tanjungpinang Culture and Tourism Office as well as the opportunities and threats that come from the external environment of the Tanjungpinang Culture and Tourism Office. Opportunities and strengths are supporting factors while threats and weaknesses are inhibiting factors for tourism development.